Nurses' Roles in Caring for Older People in Domiciliary Settings: A Scoping Review Protocol - Isabella Santomauro; Erika Bassi; Angela Durante; Consolata Bracco; Erica Busca; Silvia Caristia; Alberto Dal Molin (MDPI AG, 2024)
Due to global shifts in demographics and advances in chronic illness management over the past few decades, domiciliary care has become the primary setting for caring for older people. In this regard, nurses play a crucial role, promoting quality care and minimizing hospital admissions and the need for institutionalization. However, historical and geographic variation in nursing titles and the multitude of labels for different roles have been obstacles to the creation of a clear map outlining specific nursing roles in home care for older people. The aim of this scoping review is to map the evidence on the different nurses' roles in caring for older people in domiciliary settings. This review will include primary, secondary, and gray literature on nurses' roles in domiciliary settings for older people, sourced through comprehensive searches of various databases (MEDLINE, Embase, CINAHL) and reference scanning. No language restrictions will be applied. Two independent reviewers will conduct screening and data extraction. The tabulated results will be informed by descriptive frequencies and content analysis, presenting comprehensive findings. The review protocol was retrospectively registered within OSF database on the 23 November 2023.